Respuesta :

hbb11
12/4=3

2/2= 1

3+1=4-3=1

Answer:

The resulting value of the evaluation is 1

Step-by-step explanation:

To evaluate the expression given, we will follow the steps below;

First, we need to insert the values into given into the expression, that is;

e = 12   and f = 1/2

Inserting the values into the expression:

e/4+2f-3

12/4 +  2(1/2)  -  3

Next, is to simplify, when simplifying we should not forget to use BODMAS rule.

Simplifying the expression above, thus we have;

3 +  1  - 3

=1

Therefore, the resulting value of the evaluation is 1

ACCESS MORE